Understanding Antenatal Care Utilization Among Pregnant Women In Indonesia : A Literature Review - Kartika Aprilia (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Antenatal care (ANC) services are one of the efforts to reduce Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). However, the coverage of ANC visits has not yet reached the target, indicating the presence of factors that influence the utilization of ANC services. The objective of this study is to identify the factors influencing the use of antenatal services among pregnant women in Indonesia. This study uses a literature review design with journal articles as references. Articles were searched using the keywords "utilization," "health services," "antenatal care," and "pregnant women" through the database https://garuda.kemdikbud.go.id/. Screening was conducted on original articles published between 2019–2024, focusing on the utilization of ANC services for pregnant women in Indonesia. Eleven articles met the criteria, and information was extracted on factors associated with ANC service utilization in Indonesia. ANC service utilization is influenced by both maternal and provider factors. Maternal factors included age, knowledge level, attitude, distance to the facility, family support, economic condition, and history of complications. Service provider factors include staff support and satisfaction with services, which encourage pregnant women to be more active in ANC. Keywords: Antenatal Care, Health Service, Indonesia, Pregnant Women, Utilization.